A TOP-DOWN AND BOTTOM-UP APPROACH TO IMPROVE REGIONAL INNOVATION ECOSYSTEMS IN PORTUGAL - Resende, David Nunes; Bravo, Marco (Brazilian Journal of Operations & Production Management, 2016)
The objective of this article is to present a successful program that built a National Innovation Network based in the University Technology Transfer Offices (TTOs), incubators and science parks.The University Technology Enterprise Network (UTEN), which was launched in March 2007, includes 15 Portuguese Universities and select international partners in a 5-Year program funded by the Portuguese government. The main objective has been to accelerate the development of a sustainable, globally competitive, professional technology transfer and commercialization network within Portugal to increase Portugal’s international competitiveness in university–based science, and technology transfer and commercialization. We argue that all initiatives taken place in the project have gotten UTEN network presently run in the Open Innovation paradigm fostered mostly by the TTOs and their own networks and officers. Science and technology based entrepreneurship was increasingly seen as a key element of Portugal’s ability to grow and prosper (UTEN, 2012). Research universities had worked to foster a range of technology transfer and commercialization activities and offices, together with industrial liaison programs, mostly devoted to fostering entrepreneurial environments, launching technology based start-ups, and bringing ideas from the laboratory to the market. UTEN was created to synergize this growth and stimulate new competencies in international technology transfer and commercialization to facilitate industry access to leading markets worldwide. In other words, UTEN is the living example of an Innovation network - an Open Innovation Network launched to contribute to build the necessary relationships between all actors, giving them the necessary knowledge to play their roles. This working paper shows the actions taken to construct UTEN and improve the Portuguese Innovation Ecosystem. These actions follows the patterns observed in other studies – essentially those ones from Resende et al, 2013; McAdam et al., 2012; Philpott et al., 2011; Todorovic et al., 2011; Rogers, 2002; Rogers et al., 2001; Rogers et al., 2000 and Gibson and Rogers, 1994.We have collected data that shows the success of the program based on the results of the first five years of the project.